1999
DOI: 10.1093/intimm/11.5.765
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of anergic anti-DNA B cells: B cell anergy is a T cell-independent and potentially reversible process

Abstract: Anti-single stranded DNA (ssDNA) and anti-double stranded DNA (dsDNA) B cells are regulated in non-autoimmune mice. In this report we show that while both anti-ssDNA and anti-dsDNA B cells are blocked in their ability to differentiate into antibody-secreting cells, other phenotypic and functional characteristics distinguish them from one another. Splenic anti-ssDNA B cells are found distributed throughout the B cell follicle, and are phenotypically mature and long-lived. On the other hand, splenic anti-dsDNA B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
80
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 49 publications
4
80
1
Order By: Relevance
“…14 Thus, it has been shown that anergic B cells can be drawn into proliferation if T helper (Th)-related signals are present. 41,42 It is therefore interesting to note that numerous MZ B cells (possibly some CII-specific) have left the MZ after CII immunization and migrated into the follicles forming clusters in the B-cell zone where germinal centres normally are located. The MZ B cells may shuttle the CII into the follicle where they deposit the Ag on FO dendritic cells 27,43 and/or present CII to T cells.…”
Section: Discussionmentioning
confidence: 99%
“…14 Thus, it has been shown that anergic B cells can be drawn into proliferation if T helper (Th)-related signals are present. 41,42 It is therefore interesting to note that numerous MZ B cells (possibly some CII-specific) have left the MZ after CII immunization and migrated into the follicles forming clusters in the B-cell zone where germinal centres normally are located. The MZ B cells may shuttle the CII into the follicle where they deposit the Ag on FO dendritic cells 27,43 and/or present CII to T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Negatively selected B cells exhibit one or more of a variety of features. These include elevated expression of activation markers (30 -33), unresponsiveness to LPS and T cell-derived factors (32, 34 -36), and deficiencies in BCR signaling (31,34,36,37). However, in contrast to negatively selected cells, 6-1/V 1A B cells express normal levels of multiple activation markers (Fig.…”
Section: -1/v 1a B Cells Do Not Exhibit Evidence Of Negative Selectionmentioning
confidence: 99%
“…Anergic B cells fail to secrete Ab in response to LPS or Ag immunization due to receptor unresponsiveness (17,18,20). Some anergic B cells exhibit reduced surface IgM levels (21,22), decreased lifespan (20,23), and exclusion from the lymphoid follicle (23,24).…”
mentioning
confidence: 99%